Smart assembly of Mn-ferrites/silica core–shell with fluorescein and gold nanorods: robust and stable nanomicelles for in vivo triple modality imaging. Issue 19 (25th April 2018) - Monaco, Ilaria; Armanetti, Paolo; Locatelli, Erica; Flori, Alessandra; Maturi, Mirko; Del Turco, Serena; Menichetti, Luca; Comes Franchini, Mauro
Abstract : We report the synthesis of a resilient nanosystem (MnFe2 O4 @SiO2 @GNRs@PMs) for magnetic–photoacoustic–optical triple-modality imaging. Abstract : Herein we report the synthesis of a resilient nanosystem based on silica-coated magnetic MnFe2 O3 nanoparticles conjugated to fluorescein and PEGylated gold nanorods embedded in polymeric micelles (MnFe2 O4 @SiO2 @GNRs@PMs), for magnetic–photoacoustic–optical triple-modality imaging. The magnetic relaxivity of the nanosystem has been evaluated, revealing high r 2 / r 1 ratios that suggest the effectiveness of the nanosystem as the T 2 -contrast agent. In addition, contrast-based fluorescence imaging has been tested both in vitro and ex vivo, showing that the nanosystem exhibits the suitable optical properties of fluorescein, with contrast intensities comparable with previously reported results. Finally, photoacoustic, due to gold nanorods, performances of the nanosystem have been evaluated, revealing good linearity between concentration and photoacoustic response in the 25–250 nM concentration under irradiation at 690 nm. The results showed a contrast-to-noise ratio (CNR) as high as 60 in a mouse leg subcutaneously injected with the nanosystem. Biocompatibility studies revealed no hemolytic effect induced by the nanoconstruct, revealing the applicability of the studied diagnostic tool for medical studies.